Neuroeducation: importance of the perceptual-motors skills for learning the pyramid of human development - del Águila Camargo, Katiuska (2017)
This article allows us to show in a graphic, visual and schematic form the development process of our central nervous system, which helps us to understand the sequences and difficulties that occur in it. To do so, we have taken existing studies as reference that, added to our experience in the field of education and psychomotricity, describe the different acquisitions of human development, from the maturation of the sensory system to achieving adaptive behavior.